Download presentation
Presentation is loading. Please wait.
Published byCynthia Rice Modified over 6 years ago
1
Factoring and Simplifying Trigonometric Expressions
Dr. Shildneck
2
How to Write Powers with Trig Functions
You might see a power in two different places when using trig functions. The position of the power means different things. ππππ π = π¬π’π§β‘(π π ) = π¬π’π§β‘(πβπ) versus πππ π π = (ππππ) π = (ππππ)(ππππ)
3
Example 1 - GCF 3 ππ π 3 π₯β15 ππ π 2 π₯ 3 π’ 3 β15 π’ 2 = 3 π’ 2 (π’β5)
Let π’=ππ ππ₯ 3 ππ π 3 π₯β15 ππ π 2 π₯ 3 π’ 3 β15 π’ 2 = 3 π’ 2 (π’β5) = 3 ππ π 2 π₯(ππ ππ₯β5)
4
Example 2 β Difference of Squares
Let π’=π‘πππ₯ 4 π‘ππ 2 π₯β25 4 π’ 2 β25 = (2π’β5) (2π’+5) = (2π‘πππ₯β5) (2π‘πππ₯+5)
5
Example 3 β Quadratic Trinomial
Let π’=π πππ₯ 4 π ππ 2 π₯+π πππ₯β3 4 π’ 2 +π’β3 =(4π’β3)(π’+1) =(4π πππ₯β3)(π πππ₯+1)
6
Example 4 β Sum/Difference of Cubes
Let π’=πππ π₯ 27 πππ 3 π₯+8 27 π’ 3 +8 =(3π’+2)(9 π’ 2 β6π’+4) =(3πππ π₯+2)(9 πππ 2 π₯β6πππ π₯+4)
7
Example 4 β Rational Functions
2 π ππ 2 π₯+3π πππ₯β2 3 π ππ 2 π₯+10π πππ₯+8 2 π’ 2 +3π’β2 3 π’ 2 +10π’+8 Let π’=π πππ₯ = (2π’β1)(π’+2) 3π’+4 (π’+2) = (2π’β1) 3π’+4 = (2π πππ₯β1) 3π πππ₯+4
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.